A Study on Usage of OR for Dynamic Industrial Problems: Exploring the Applications of Mathematical Models in Solving Industrial Problems (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This paper explains how comparatively simple mathematical models can address such industrial problems. Models may also be used to provide an overview into the interaction of manufacturing processes. This paper is beneficial for students at the master's level in explaining both the model and the modeling function. This review of models can be helpful for students who are involved in solving specific industry problems. Various forms of manufacturing challenges have been addressed.